Comparison of PD-1 Inhibitors in Patients With Advanced Esophageal Squamous Cell Carcinoma in the Second-Line Setting - Zhou, Yi-Xin; Chen, Ping; Sun, Yu-Ting; Zhang, Bei; Qiu, Miao-Zhen (Frontiers in Oncology, 2021)
Background KEYNOTE-181, ATTRACTION-3, and ESCORT trials have opened the era of programmed death 1 (PD-1) inhibitors in the second-line therapy for esophageal squamous cell carcinoma (ESCC). There is no head-to-head comparison of pembrolizumab vs. nivolumab vs. camrelizumab in the second-line setting for ESCC. We performed an indirect comparison to explore the optimal choice of immune checkpoint inhibitor (ICI) for advanced ESCC. Methods Patients in ATTRACTION-3 and ESCORT were all squamous carcinoma, while KEYNOTE-181 enrolled both adenocarcinoma and squamous carcinoma patients. We only extract information of patients with squamous carcinoma from KEYNOTE 181 study and all the patients from ATTRACTION-3 and ESCORT. The main clinical outcomes for this study were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and treatment-related adverse events (TRAEs). Results Indirect analysis showed similar survival benefit among three PD-1 inhibitors. Nivolumab was comparable with pembrolizumab in most subgroups except that nivolumab was slightly better for patients with performance status (PS) score of 1 [HRnivo/pembro: 0.68 (95% confidence interval (CI): 0.45–1.02], p = 0.07). Compared with nivolumab indirectly, pembrolizumab and camrelizumab had better PFS [HRpembro/nivo: 0.85 (95% CI: 0.63–1.14), p = 0.29; HRcam/nivo: 0.64 (95% CI: 0.47–0.87), p = 0.004] and significantly higher ORR [RRpembro/nivo: 2.51 (95% CI: 1.22–5.15), p = 0.01; RRcam/nivo: 3.52 (95% CI: 1.73–7.18), p = 0.001]. Compared with camrelizumab indirectly, pembrolizumab had slightly worse PFS [HRpembro/cam: 1.33 (95% CI: 0.99–1.79), p = 0.057] and comparable ORR [RRpembro/cam: 0.71 (95% CI: 0.32–1.60; p = 0.41)]. Camrelizumab had a significantly higher rate of all grade TRAEs than both pembrolizumab and nivolumab. Conclusions Combining the safety and potential survival benefit, we recommend nivolumab for ESCC patients with PS score of 1 and pembrolizumab or camrelizumab for patients with better PS and seeking for higher efficacy or longer PFS.